Nurture groups in school and at home : connecting with children with social, emotional and behavioural difficulties - Cooper, Paul, 1955- (Innovative learning for all., 2007)
This book explores the ways in which pupils with social, emotional and behavioural difficulties can be effectively engaged in schooling - either in school or at home. It explains the social and emotional underpinnings of learning and presents practical strategies for aiding engagement. Nurture groups, originally devised and implemented in the 1970s, are specially designed classes that cater for pupils having difficulties in adjusting to the requirements of mainstream classrooms. Paul Cooper and Yonca Tiknaz present evidence of the success of nurture groups from the perspectives of the ch.